STATUS GIZI DAN HUBUNGANNYA DENGAN LAMA RAWAT INAP DAN INFEKSI PASCA OPERASI PASIEN LANSIA DI BANGSAL BEDAH RSUP DR. SARDJITO YOGYAKARTA - , YOSEPHIN ANANDATI PRANOTO; , Susetyowati, DCN, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Hospital malnutrition still become main problem in health area. 78,3% patients found to be malnourished in hospital care. Group of patients with highest prevalence of malnutrition in surgical patients (52,5%) and geriatric patients (among other age-groups). Many research proved that nutritional status in patients significantly correlated with length of stay and post operative complications (including post operative infection). MNA and GNRI are methods that can be used for assessing nutritional status in geriatric patients. Objective: To validate GNRI as a nutritional assessment tool compare with MNA and to analyze the association between nutritional status of patients with length of stay and post operative complication. Method: This is an analytic cross sectional study that is held in Adult Surgery Department of RSUP Dr. Sardjito Yogyakarta along March-November 2012. 67 geriatric patients with surgical treatment are assessed their early nutritional status with MNA and GNRI. Followed by record of their date of admission and submission and also their incidence of post operative infection (taken from medical record data). Validity test is done by calculating sensitivity, specificity and MSS value of GNRI and bi-variate analyze with chi square. Results: Based on its validity test GNRI sensitivity is 82,14% and specificity 63,64% (MSS 145,78%). Patients with nutritional risk status with longer length of stay is 58,9% assessed with MNA and 54% with GNRI. Patients with no risk of malnutrition assessed with MNA and having no post operative infection is 72,7% and 70,6% while assessed with GNRI. Chi square analyze shows no association between nutritional status with length of stay and post operative infection in geriatric patients assessed with GNRI and MNA (p>0,05). Conclusion: There are no association between nutritional status with length of stay and post operative infection in geriatric patients assessed with GNRI and MNA.